High-quality genome assembly of the soybean fungal pathogen Cercospora kikuchii. Issue 10 (5th August 2021) - Kashiwa, Takeshi; Suzuki, Tomohiro
Abstract: Plant diseases caused by the Cercospora genus of ascomycete fungi are a major concern for commercial agricultural practices. Several Cercospora species can affect soybeans, such as Cercospora kikuchii which causes soybean leaf blight. Speciation in Cercospora on soybean has not been adequately studied. Some cryptic groups of Cercospora also cause diseases on soybean. Moreover, it has been known C . kikuchii population genetic structure is different between countries. Consequently, further genomic information could help to elucidate the covert differentiation of Cercospora diseases in soybean. Here, we report for the first time, a chromosome-level genome assembly for C . kikuchii . The genome assembly of 9 contigs was 34.44 Mb and the N50 was 4.19 Mb. Based on ab initio gene prediction, several candidates for pathogenicity-related genes, including 242 genes for putative effectors, 55 secondary metabolite gene clusters, and 399 carbohydrate-active enzyme genes were identified. The genome sequence and the features described in this study provide a solid foundation for comparative and evolutionary genomic analysis for Cercospora species that cause soybean diseases worldwide.